The Good Behaviour Game intervention to improve behavioural and other outcomes for children aged 7-8 years: a cluster RCT - Neil Humphrey; Alexandra Hennessey; Patricio Troncoso; Margarita Panayiotou; Louise Black; Kimberly Petersen; Lawrence Wo; Carla Mason; Emma Ashworth; Kirsty Frearson; Jan R Boehnke; Rhys D Pockett; et al. (NIHR Journals Library, 2022)
Background: Universal, school-based behaviour management interventions can produce meaningful improvements in children's behaviour and other outcomes. However, the UK evidence base for these remains limited. Objective: The objective of this trial was to investigate the impact, value for money and longer-term outcomes of the Good Behaviour Game. Study hypotheses centred on immediate impact (hypothesis 1); subgroup effects (at-risk boys, hypothesis 2); implementation effects (dosage, hypothesis 3); maintenance/sleeper effects (12- and 24-month post-intervention follow-ups, hypothesis 4); the temporal association between mental health and academic attainment (hypothesis 5); and the health economic impact of the Good Behaviour Game (hypothesis 6). Design: This was a two-group, parallel, cluster-randomised controlled trial. Primary schools (n = 77) were randomly assigned to implement the Good Behaviour Game for 2 years or continue their usual practice, after which there was a 2-year follow-up period. Setting: The trial was set in primary schools across 23 local authorities in England. Participants: Participants were children (n = 3084) aged 7-8 years attending participating schools. Intervention: The Good Behaviour Game is a universal behaviour management intervention. Its core components are classroom rules, team membership, monitoring behaviour and positive reinforcement. It is played alongside a normal classroom activity for a set time, during which children work in teams to win the game to access the agreed rewards. The Good Behaviour Game is a manualised intervention delivered by teachers who receive initial training and ongoing coaching. Main outcome measures: The measures were conduct problems (primary outcome; teacher-rated Strengths and Difficulties Questionnaire scores); emotional symptoms (teacher-rated Strengths and Difficulties Questionnaire scores); psychological well-being, peer and social support, bullying (i.e. social acceptance) and school environment (self-report Kidscreen survey results); and school absence and exclusion from school (measured using National Pupil Database records). Measures of academic attainment (reading, standardised tests), disruptive behaviour, concentration problems and prosocial behaviour (Teacher Observation of Child Adaptation Checklist scores) were also collected during the 2-year follow-up period. Results: There was no evidence that the Good Behaviour Game improved any outcomes (hypothesis 1). The only significant subgroup moderator effect identified was contrary to expectations: at-risk boys in Good Behaviour Game schools reported higher rates of bullying (hypothesis 2). The moderating effect of the amount of time spent playing the Good Behaviour Game was unclear; in the context of both moderate (≥ 1030 minutes over 2 years) and high (≥ 1348 minutes over 2 years) intervention compliance, there were significant reductions in children's psychological well-being, but also significant reductions in their school absence (hypothesis 3). The only medium-term intervention effect was for peer and social support at 24 months, but this was in a negative direction (hypothesis 4). After disaggregating within- and between-individual effects, we found no temporal within-individual associations between children's mental health and their academic attainment (hypothesis 5). Last, our cost-consequences analysis indicated that the Good Behaviour Game does not provide value for money (hypothesis 6). Limitations: Limitations included the post-test-only design for several secondary outcomes; suboptimal implementation dosage (mitigated by complier-average causal effect estimation); and moderate child-level attrition (18.5% for the primary outcome analysis), particularly in the post-trial follow-up period (mitigated by the use of full information maximum likelihood procedures). Future work: Questions remain regarding programme differentiation (e.g. how distinct is the Good Behaviour Game from existing behaviour management practices, and does this makes a difference in terms of its impact?) and if the Good Behaviour Game is impactful when combined with a complementary preventative intervention (as has been the case in several earlier trials). Conclusion: The Good Behaviour Game cannot be recommended based on the findings reported here. Trial registration: This trial is registered as ISRCTN64152096. Funding: This project was funded by the National Institute for Health and Care Research (NIHR) Public Health Research programme and will be published in full in Public Health Research; Vol. 10, No. 7. See the NIHR Journals Library website for further project information.